Three Transcription Factors, HFR1, LAF1 and HY5, Regulate Largely Independent Signaling Pathways Downstream of Phytochrome A - Jang, In-Cheol (Oxford University Press, 2013)
Among signaling components downstream of phytochrome A (phyA), HY5, HFR1 and LAF1 are transcription factors that regulate expression of phyA-responsive genes. Previous work has shown that FHY1/FHL distribute phyA signals directly to HFR1 and LAF1, both of which regulate largely independent pathways, but the relationship of HY5 to these two factors was unclear. Here, we investigated the genetic relationship among the genes encoding these three transcription factors, HY5, HFR1 and LAF1. Analyses of double and triple mutants showed that HY5, a basic leucine zipper (bZIP) factor, HFR1, a basic helix–loop–helix (bHLH) factor, and LAF1, a Myb factor, independently transmit phyA signals downstream. We showed that HY5 but not its homolog, HYH, could interact with HFR1 and LAF1; on the other hand, FHY1 and its homolog, FHL did not interact with HY5 or HYH. Together, our results suggest that HY5 transmits phyA signals through an FHY1/FHL-independent pathway but it may also modulate FHY1/FHL signal through its interaction with HFR1 and LAF1.